Implementasi Metode Multi-Agent Untuk Mendeteksi Rogue Access Point (RAP) - Dhimas Satriawan Utama; Dany Primanita Kartikasari; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless Local Area Network (WLAN) is a technology that is very popular with the public. The reason is because the user is not bothered with the length of the cable that must be connected to the device. However, there are weaknesses that can harm the user actively or passively. The weakness of this technology is that the transmission media is too open and a weak encryption scheme that can provide a path for hackers to enter the network. Rogue Access Point (RAP) is one of the most dangerous attacks on this technology. Thus, this study aims to detect RAP on the network. To achieve the objectives of this study, a Multi-Agent method is used to detect the presence of RAP on the network. The Multi-Agent method used in this study consists of a Master Agent and a Slave Agent to detect RAP. The Master Agent is pinned on the Network Manager device while the Slave Agent is pinned on the PC Staff. Slave Agent acts as a sensor while the Master Agent has the role to decide whether the findings from Slave are RAP or not. The results of the study were obtained based on two tests, namely the accuracy test resulted in 80% of the ten experiments while the detection time obtained a value of 1.94 seconds. The conclusion of this research is the Multi-Agent method successfully detected the presence of RAP on the network resulting in an 80% value for the accuracy test and 1.94 seconds for the detection time test. So, the Multi-Agent method can detect RAP well.